Stiffness modulation-driven transfer printing and strain isolation in stretchable electronics - Di Guo; Yan Li; Qing Zhao; Pai Liu; Lixuan Che; Zhan Kang; Ming Li; Yangjun Luo (Materials & Design, 2022)
Stretchable electronics, overcoming mismatch between rigid circuit and soft biology and withstanding overstretching before electrical/mechanical failure, enables attractive and prominent applications which are impossible for conventional electronics. Transfer printing and strain isolation techniques play important roles in fabricating and using of stretchable electronics. In this manuscript, driven by stiffness modulation and topology optimization, an easy-to-implement, reversible and scalable transfer printing with programmable adhesion switchability through only mechanical stimulus, and a strain isolation significantly reducing strain and effectively shielding active electronics from extreme elongation are proposed. The related performance and mechanism are respectively investigated through physical experiment and theoretical model. This study can be exploited as design guideline for stretchable electronics.